Lonchaeidae (Diptera) aus Afrika südlich der Sahara mit Beschreibung von drei neuen Arten. - Morge, Günter (Contributions to Entomology = Beiträge zur Entomologie, 1980)
The evaluation of results of expeditions established new finds of Lonchaeidae in Africa south of the Sahara which are added to those formerly known; threen new species of the genera Dasiops Rondani and Lamprolonchaea Bezzi described, and keys to the species of both genera known from this region are given. Nomenclatural Actskarneri Morge, 1980 (Dasiops), spec. n.lindneri Morge, 1980 (Lamprolonchaea), spec. n.ponti Morge, 1980 (Lamprolonchaea), spec. n.